Star polymer synthesis via λ-orthogonal photochemistry. Issue 60 (5th July 2016) - Hiltebrandt, Kai; Kaupp, Michael; Molle, Edgar; Menzel, Jan P.; Blinco, James P.; Barner-Kowollik, Christopher
Abstract : λ-Orthogonal photo-induced ligation in two directions is introduced via a modular, light driven selective star shaped polymer formation. Abstract : We introduce a light induced sequence enabling λ-orthogonal star polymer formation via an arms-first approach, based on an α, ω-functional polymer carrying tetrazole and o -methyl benzaldehyde moieties, which upon irradiation can readily undergo cycloaddition with a trifunctional maleimide core. Depending on the wavelength, the telechelic strand can be attached to the core at either photo-reactive end.